If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -15n = 5(-3 + z) 2 + -15n = (-3 * 5 + z * 5) 2 + -15n = (-15 + 5z) Solving 2 + -15n = -15 + 5z Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -15n = -15 + -2 + 5z Combine like terms: 2 + -2 = 0 0 + -15n = -15 + -2 + 5z -15n = -15 + -2 + 5z Combine like terms: -15 + -2 = -17 -15n = -17 + 5z Divide each side by '-15'. n = 1.133333333 + -0.3333333333z Simplifying n = 1.133333333 + -0.3333333333z
| -3x^2+24x-45=0 | | -3(-2x+1)-5=10 | | 15=6x-3x | | 3(x-4)+6=2x | | 3(q-5)=4a-(2a+4) | | 9(2K+3)+2=11(11K-11K) | | X-3x-10=90 | | x/6+14=0 | | 2x+7(2x-16)=48 | | 2x+7=-2x+5 | | 5r-18r-6=111 | | 6=-7/9+v | | 33333333n=33333333 | | [8(z+4)-19]-2(z-3)+2= | | 1/5a-27=7 | | 5x+6+1=17 | | -16=-1+4n+1 | | 6+14=0 | | 9(2K+3)+2=11(K-k) | | 4x-8+4x=-16 | | 3b-3=4b+9 | | -4x-4=36 | | 12x/12=35/12 | | 9=2r-3+6 | | 2x+1=x+111 | | 2x+7=2x+5 | | (3x+2y-1)dx=(2x-3y+1)dy | | -11/9x3/10 | | 8s-10=27-(3s-7) | | x+4+6x=-3 | | 3x+10x-(5x+9)= | | 1/3a-2=15 |